Minimizing the Bright/Shadow Focal Spot Size with Controlled Side-Lobe Increase in High-Numerical-Aperture Focusing Systems. (20th November 2013) - Khonina, S. N.; Volotovskiy, S. G.
Abstract : Minimizing the bright/shadow focal spot size for differently polarized incident waves through the additional apodization of the focusing system output pupil by use of an optical element with the vortex phase dependence on angle and the polynomial amplitude dependence on radius is studied. The coefficients of the radial polynomial were optimized with the aim of fulfilling certain conditions such as the energy efficiency preservation and keeping the side lobes under control. The coefficients were chosen so as to minimize the functional using Brent's method.